1997
DOI: 10.1076/phbi.35.1.43.13262
|View full text |Cite
|
Sign up to set email alerts
|

Activity-directed Isolation of Spasmolytic (anti-cholinergic) Alkaloids from Brugmansia arborea (L.) Lagerheim

Abstract: This paper examined the effects of the extracts MeOH and H 2 O, chromatographic fractions and three pure alkaloids from Brugmansia arborea (L.) Lagerheim (Solanaceae) on the electrically-and acetylcholine (Ach)-induced contractions of isolated guinea-pig ileum. The results indicate that both MeOH and H 2 O extracts dose-dependently reduced the electrical contractions of guinea-pig ileum. Furthermore, the partially purified fractions 2 and 3 from MeOH extract and three pure compounds obtained from the fraction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
21
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 4 publications
4
21
0
Order By: Relevance
“…This is in accordance with the literature, in which there are reports that the genus Brugmansia contains this class of alkaloids [9, 19]. …”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…This is in accordance with the literature, in which there are reports that the genus Brugmansia contains this class of alkaloids [9, 19]. …”
Section: Resultssupporting
confidence: 93%
“…Drug addiction can be considered as a disorder of DA-dependent associative learning [24], and the fact that CPP and the hyperactivity induced by morphine are blocked by B. arborea extract suggests that this plant undermines the development of opiate addiction. Another possible explanation for the results obtained is the strong anticholinergic activity reported for a methanol extract of B. arborea [9]. Recent evidence implicates muscarinic acetylcholine receptors in the behavioral effects of drugs of abuse such as morphine and cocaine.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…This result agrees with the available literature that reports that the genus Brugmansia contains this class of alkaloids [3]. …”
Section: Resultssupporting
confidence: 93%
“…Moreover, recent review showed that certain alkaloids are medicinally applied as local anesthetic [70], stimulants -(caffeine, nicotine, threobromine, methylated derivatives of xanthine, methylated uric acids such as theacrine, methylliberine and libertine [7]), psychedelics, analgesics -(morphine [72,73], codeine [41], N-methyl-N-deethylaconitine [74]), bactericidal-(piperidine [75], harmandiamines A-C [76]), anti-cancer drugs -(camptothecin, vinblastine, vincristine [7,77]), anti-hypertensive agents -(serpentine [78][79][80][81]), cholinomimerics -(aceclidine [41]), spasmolysis agents - [82], vasodilators -(rutaecarpine [83]), anti-arrhythmia, anti-asthma [41], anti-malarials (quinine and artemisinin [7]) etc.…”
Section: Isolation Identification and Characterization Of Bioactive mentioning
confidence: 99%